Application of WCAG Standards as a Basis for Visual Design Assessment in Running Applications - Nicklaus Arthur; Marina Wardaya (Universitas Ciputra Surabaya, 2026)
This research studied how accessible running apps are visually, utilizing the Web Content Accessibility Guidelines (WCAG). The purpose of this study was to test four UI elements, buttons, icons, text, and labels and provide recommendations for their visual accessibility. This study was of a quantitative audience, looking at color contrast ratios for moving text over backgrounds while at the same time looking at compliance with the WCAG AAA and AA standards when testing UI elements from all three apps. Data was collected from the Strava, Nike Run, and Adidas Running apps in the Home, Activity Tracking, and Result/Summary screens. The results indicated that the primary UI elements, primary buttons and any numeric displays, were found to mostly pass the AAA and AA WCAG billing standards, while secondary UI elements, unit labels, routes map lines, and subtexts, were often found to not pass the AAA standards, and in some cases did not even pass the AA standards. This study provides designer resources, such as heat maps and tables that show pass/fail ratios for each UI element. This study demonstrates that WCAG was an effective basis for developing an accessible visual design that supported readable text which engaged all users. This study also helped by blending accessible visual design evaluation within WCAG framework for running app interfaces.